Concepts in Cancer Modeling: A Brief History - Thomas, Renee M. (Cancer Res, 2016)
Modeling, an experimental approach to investigate complex biological systems, has significantly contributed to our understanding of cancer. While extensive cancer research has been conducted utilizing animal models for elucidating mechanisms and developing therapeutics, the concepts in a good model design and its application have not been well elaborated. In this review, we discuss the theory underlying biological modeling and the process of producing a valuable and relevant animal model. Several renowned examples in the history of cancer research will be used to illustrate how modeling can be translatable to clinical applications. Finally, we will also discuss how the advances in cancer genomics and cancer modeling will influence each other going forward.